Dietary Component-Induced Inflammation and Its Amelioration by Prebiotics, Probiotics, and Synbiotics - Bilal, Muhammad; Ashraf, Shoaib; Zhao, Xin (Frontiers in Nutrition, 2022)
A balanced diet with many dietary components maintains immune homeostasis directly by interacting with innate and adaptive immune components or indirectly through gut microbiota and their metabolites. Dietary components may inhibit pro-inflammatory mediators and promote anti-inflammatory functions or vice versa. Western diets with imbalanced dietary components skew the immune balance toward pro-inflammation and induce intestinal inflammation, consequently leading to many intestinal and systemic inflammatory diseases like ulcerative colitis, Crohn's disease, irritable bowel syndrome, cardiovascular problems, obesity, and diabetes. The dietary component-induced inflammation is usually chronic in nature and frequently caused or accompanied by alterations in gut microbiota. Therefore, microbiome-targeted therapies such as probiotics, prebiotics and synbiotics hold great potentials to amend immune dysregulation and gut dysbiosis, preventing and treating intestinal and systemic inflammatory diseases. Probiotics and prebiotics are progressively being added to foods and beverages, with claims of health benefits. However, the underlining mechanisms of these interventions for preventing and treating dietary component-induced inflammation are still not very clear. In addition, possibly ineffective or negative consequences of some probiotics, prebiotics and synbiotics call for stringent testing and regulation. Here, we will first briefly review inflammation, in terms of its types and the relationship between different dietary components and immune responses. Then, we focus on current knowledge about the direct and indirect effects of probiotics, prebiotics and synbiotics on intestinal and systemic inflammation. Understanding how probiotics, prebiotics and synbiotics modulate the immune system and gut microbiota will improve our strategies for preventing and treating dietary component-induced intestinal inflammation and inflammatory diseases.